Protective Effect of Sodium Selenite and Vitamin E in Physiological and Histological Parameters on Male Rats Treated with Lithium Carbonate - Afyaa Sabah Nasir (Journal of Global Pharma Technology, 2018)
The current study was designed to determine the antioxidant effects of sodium selenite and vitamin E against oxidative stress induced by lithium carbonate in physiological blood parameters and histological parameters include (liver and kidney) on the adult male rats. The study was conducted in the animal house of the Faculty of Science/University of Kufa on 30 animals of adult male rats aged 2.5-3 months and the weight of 200-250 gm. The adult male rats which were divided randomly into five groups each group contains six animals, the first group promised to negative control which were administrated normal saline only, the second group administrated lithium carbonate at dose 4 mg/kg of body weight per day and promised as positive control, the third group administrated lithium carbonate at dose 8 mg/kg of body weight per day  also promised as positive control, the fourth group administrated lithium carbonate at dose 4 mg/kg of body weight per day with the solution containing to sodium selenite at dose of 2.4 mg/ml and vitamin E at  dose of 60 mg/ml daily and  the fifth group administrated lithium carbonate at dose 8 mg/kg of body weight per day with the solution containing to sodium selenite at dose of 2.4 mg/ml and vitamin E at  dose of 60 mg/ml daily,  for a period of eight weeks. after eight weeks the rats were sacrificed for  taking blood samples and removing the liver, kidney.   After the end of experiment the results showed the presence of a significant decrease (p<0.05) in the red blood corpuscles counts, haemoglobin concentration and hematocrit while significant increase (p<0.05) in the white blood cells counts and  erythrocyte sedimentation rate in the animals treated with lithium carbonate compared to the control group for eight weeks While the results show (p<0.05) significant increase (p <0.05) in the red blood corpuscles counts, haemoglobin concentration, hematocrit, as well as a significant decrease (p<0.05) in the white blood cells rate and erythrocyte sedimentation rate in the animals treated with lithium carbonate with sodium selenite with vitamin E compared with the control group for eight weeks. The results indicated a significant increase (p<0.05) in the Aspartate aminotransferase, Alanine aminotransferase & Alkaline phosphatase in the animals treated with lithium carbonate only compared to the control group for eight weeks of administration at the same time occur a significant decrease (p <0.05) in the liver enzyme levels in the treated animals with lithium carbonate, sodium selenite and vitamin E for a period of eight weeks compared with control group. Finally, the results of histopathological changes showed sever degeneration, vascular congestion in the liver and noticed degenerative cells with haemorrhage in the kidney in the group of rats treated by lithium carbonate while appeared improvement in the liver, kidney in the groups’ administrated lithium carbonate with lithium carbonate with sodium selenite, vitamin E. The study conclude  sodium selenite and vitamin E have effective antioxidants against oxidative stress induced by oral administration of lithium carbonate led to improve the physiological parameters and histopathological changes compared with control group.Keywords: Oxidative stress, Sodium selenite, Vitamin E and lithium carbonate.